Quantifying Adsorption of an Indicator Bacteria In A Soil - Water System - Ling, T. Y. (American Society of Agricultural Engineers, 2002)
Two experiments were conducted to investigate and quantify the weak and strong adsorption of an indicator bacterium (Escherichia coli) in soil-water systems composed of Tangi silt loam (14% clay) or Commerce clay loam (35% clay). Percent adsorption of E. coli was significantly higher in Commerce clay loam than in Tangi silt loam for both weak and strong adsorption. The distribution coefficient of weak adsorption of E. coli in the Commerce soil-water system was found to be significantly higher than that of strong adsorption. However, the distribution coefficient of weak adsorption of E. coli in the Tangi soil-water system was found to be significantly lower than that of strong adsorption. For strong adsorption, together with literature data, a high correlation (R2 = 0.89) was found between percent adsorption and clay content.Significant correlation (R2 = 0.67) was found between distribution coefficient and clay content. The relationships developed may be used for modeling purposes.